2018
DOI: 10.1101/363853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Both rare and common genetic variants contribute to autism in the Faroe Islands

Abstract: The number of genes associated with autism is increasing, but few studies have been performed on epidemiological cohorts and in isolated populations. Here, we investigated 357 individuals from the Faroe Islands including 36 individuals with autism, 136 of their relatives and 185 non-autism controls. Data from SNP array and whole exome sequencing revealed that individuals with autism compared to controls had a higher burden of copynumber variants (p < 0.05), higher inbreeding status (p < 0.005) and higher load … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…For the Hip‐adult group, there are 12 hub genes identified, including Kdr , S1pr1 , Ubc , Grm2 , Grin2b , Nrxn1 , Pdyn , Grin3a , Itgam , Grin2a , Gabra2 , and Camk4 . Among them, Grin2b , Nrxn1 , Grin2a , Gabra2 , and Camk4 have been associated with ASD based on human genetics evidence, indicating that this integrated analysis indeed enriched genes that are important for ASD [Gonzalez‐Nunez, ; Leblond et al, ; Tarabeux et al, ; Zech et al, ]. Moreover, the other genes including Kdr , S1pr1 , Ubc , Grm2 , Pdyn , and Itgam are possible candidates for ASD due to the related molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…For the Hip‐adult group, there are 12 hub genes identified, including Kdr , S1pr1 , Ubc , Grm2 , Grin2b , Nrxn1 , Pdyn , Grin3a , Itgam , Grin2a , Gabra2 , and Camk4 . Among them, Grin2b , Nrxn1 , Grin2a , Gabra2 , and Camk4 have been associated with ASD based on human genetics evidence, indicating that this integrated analysis indeed enriched genes that are important for ASD [Gonzalez‐Nunez, ; Leblond et al, ; Tarabeux et al, ; Zech et al, ]. Moreover, the other genes including Kdr , S1pr1 , Ubc , Grm2 , Pdyn , and Itgam are possible candidates for ASD due to the related molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five genes intersected by rare loss events, RIMS2 was also intersected by a rare gain found in another individual of the ASD cohort. No study so far has reported the association of RIMS2 with genetic disorders, but its homologues RIMS3 and RIMS4 were implicated autism risk factors (Kumar et al, 2010; Leblond et al, 2018). RIMS2 codes for a presynaptic protein regulating synaptic membrane exocytosis, and mediates neurotransmitter release during short- and long-term synaptic plasticity (Kaeser and Südhof, 2005).…”
Section: Discussionmentioning
confidence: 99%